Стохастичне моделювання міцності матеріалів з поверхневими дефектами - Квіт, Роман (КІНПАТРІ ЛТД, 2013)
Analytical and numerical strength investigations of plate with random by size and distribution surface defects are carrying out. The expressions for limit loading distribution function under different stress state forms are obtained. The influence of loading, stress state form, defect number and material homogeneity on the probability of failure is explored.
Stochastic simulation of materials strength with surface defects